The efforts increasing the knowledge of breastfeeding mothers about oxytocin massage in enhancing breast milk production - Amiruddin, Ainun; Siregar, Nilda yulita; Noya, Fransisca; Nurfatimah, Nurfatimah; Longgupa, Lisda Widianti (Universitas Muhammadiyah Magelang, 2021)
Breast milk is the main source nutrition for babies who are not yet able to digest solid food. Breast milk is very useful given for baby during the first 6 months of life. The phenomenon encountered today is that the coverage of breast milk is decreasing day by day with various factors causing it. Oxytocin massage is one of the efforts to facilitate the production of breast milk with a mechanism that can trigger the release of prolactin and oxytocin, hormones needed to secrete breast milk. The purpose of this activity is increasing the knowledge of breastfeeding mothers about oxytocin massage in enhancing breast milk production. This activity was carried out in Landangan Village on October 15, 2020. The target of this activity was breastfeeding mothers. The method used in this community service was distributing pre-test sheets, followed by providing counseling using leaflet media and ending with filling out post-test sheets. The results of the evaluation through filling out the pre-posttest questionnaire showed an increase in the level of knowledge of breastfeeding mothers. The average level of knowledge before counseling was 60 and the average after counseling was 82.